What Makes HFTs Tick? Tick Size Changes and Information Advantage in a Market with Fast and Slow Traders - Chaboud, Alain P.; Dao, Avery; Vega, Clara; Zikes, Filip (Management Science, 2024)
We study the impact of two changes in the minimum tick size, a reduction and a subsequent increase, on the trading behavior of fast and slow traders in the spot foreign exchange market. We find that the most notable impact of the tick size reduction is a substantial increase in the liquidity demand of high-frequency traders (HFTs) and not the decrease in their liquidity provision discussed by prior literature. We show that this change in behavior is linked to the higher frequency of price signals that arises with the smaller tick size and to the ability of fast traders to profit from it, often at the detriment of slower traders. Following the tick size decrease and the increase in liquidity demand by HFTs in the spot market, the role of the spot market in price discovery drops relative to that of the futures market. We discuss these findings in the context of the impact of HFTs on the information content of financial markets. This paper was accepted by Agostino Capponi, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2022.02935 .